Pengelolaan Biaya Operasional Pendidikan Raudhatul Athfal Nurul Huda Bogor Tahun Pelajaran 2022/2023 - Alifia Taufika Rahmah; Sita Ratnaningsih; Nurochmin (TADBIR MUWAHHID, 2023)
Early Childhood Education as an educational institution to educate the life of the nation needs support from the central, regional and community levels. With that, the government launched the PAUD Education Operational Assistance (BOP) program. However, in practice, it is felt that the provision of BOP is no longer relevant to the real needs of students. This fact is due to the amount of BOP funds until 2020 has not changed and has not followed various economic conditions (inflation). This study aims to describe the management of the operational costs of Raudhatul Athfal Nurul Huda Bogor's education, especially in the 2022/2023 school year. This type of research uses qualitative data collection techniques through interviews, observation and documentation. The results of the study prove that the management of the operational costs of the Raudhatul Athfal Nurul Huda Bogor education is going well, because there is a planning process by holding an association between school principals, administration, teachers and school committees to make an activity budget for the next one year and collect requirements for disbursing Educational Operational Assistance from the government. In practice, the sources of funds received from both the government and parents of students have been allocated properly. This BOP is supervised by the school principal, teacher council and the chairman of the foundation as internal supervisors and supervisors from the sub-district as external supervisors.